Reward and recognition for employee motivation in Nepalese microfinance institutions - Lamichhane, Basu Dev; Bhaumik, Amiya; Gnawali, Achyut; Lama, Padam Bahadur (International Journal of Management and Sustainability, 2024)
The main purpose of this study was to examine the impact of intrinsic, extrinsic reward, and recognition on employee motivation in Nepalese microfinance institutions. To obtain this objective, a descriptive and causal relational research design was used in the study. Cross-sectional data were used, comprising a structured questionnaire, and distributed among 300 employees of Microfinance Institutions (MFIs) using simple random sampling. Out of which, 191 (63.67%) useful questionnaires were received. The correlation and regression analysis of the study revealed that extrinsic reward and recognition had a positive and significant relationship with employees’ motivation. The findings of study indicated that the higher the level of extrinsic reward and recognition in the MFIs, the higher the employee motivation, which leads towards the higher sustainability of the MFIs. However, intrinsic reward had an insignificant relationship with motivation. Further, this study contributes to the field of employee management in the organization and establishes the foundation for adaptation and application of employee motivation while increasing outreach, loan portfolio quality, poverty alleviation, and business promotion in the field of microfinance institutions. The results of the study will be useful to regulatory authorities, Human Resource (HR) analysts, Banking and Financial Institutions (BFIs), and MFIs. Subsequent research in the same discipline that encompasses the more general areas of study ought to be done.